Does Antidumping Protection raise Market Power of Domestic Firms? Evidence from Firm Level Data - Jozef Konings; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2002)
This paper estimates how anti-dumping (AD) protection affects the market power of firms. To this end, we use a rich panel data set of 1,666 EU producers that were involved in AD cases initiated in 1996 to estimate markups of price over marginal cost. Our findings indicate that markups in most cases increase significantly in the period when firms enjoy AD protection compared to a period before protection. In industries where competition is very tough before protection, we fail to find an increase in markups, while in industries with some market power before protection, trade policy raises markups between 3% points and 15 % points, depending on the sector. Our results are robust to alternative specifications and estimation techniques. Our findings are also consistent with recent theoretical models that deal with the economic effects of firm behavior in response to AD protection
Keywords: F13; L13; L41; 330; market power; price-cost markups; antidumping cases; European producers; Antidumping; Protektionismus; Internationaler Wettbewerb; Marktmacht; Betriebliche Preispolitik; Gewinn; EU-Staaten